Analysis of fast-ion Dα data from the National Spherical Torus Experiment. (6th April 2016) - Heidbrink, W.W.; Ruskov, E.; Liu, D.; Stagner, L.; Fredrickson, E.D.; Podestà, M.; Bortolon, A.
Abstract: Measured fast-ion D α (FIDA) data from an extensive NSTX database are compared to 'classical' predictions that neglect transport by instabilities. Even in the absence of appreciable MHD, in many cases, the profile peaks at smaller major radius and the profile is broader than the predictions. Abrupt large-amplitude MHD events flatten the FIDA profile, as do most toroidal Alfvén eigenmode (TAE) avalanche events. Generally, the onset of a long-lived mode also flattens the FIDA profile.